Desenvolvimento do protocolo de instrumentos para verificar a eficácia do programa iSupport-Brasil para cuidadores informais de pessoas que vivem com demência - Pilegis, Anabel Machado Cardoso Alvarenga (Universidade Federal de São Carlos, 2023)
Due to the length of time that caregivers spend helping their family member living with dementia and the conditions under which this involvement tends to occur, it is common for the caregiver to develop physical and psychological health problems. Urge to initiatives that focus on the well-being and quality of life of these caregivers. In this scenery, the iSupport-BR program emerges, being a psychoeducational tool focused on the needs of caregivers of people living with dementia. There is a demand to evaluate the effects of this program for informal caregivers, through a sensitive evaluation protocol that assesses the domains impacted by iSupport. Objectives: To describe the process of developing a protocol to assess the effects of the iSupport-Brazil program on the mental health and well-being of informal caregivers of people living with dementia. Method: This is a multicenter, methodological study, carried out between 2020 and 2022, to describe the elaboration process of the protocol to assess the effects of the iSupport-Brazil program, consisting of six main steps. The procedures adopted for this study were: (1) Detailed analysis of the protocol developed by WHO; (2) Detailed analysis of the protocols developed by other countries that adhered to the iSupport program, of WHO; (3) Qualitative and comparative analysis of the protocols' instruments; (4) Development of the protocol, in electronic form; (5) Pilot study on the application of the protocol; (6) Development of the final version of the protocol to evaluate the effects of the iSupport-BR program. Results: Detailed description of the development of a protocol that addresses universal issues, related to outcomes related to informal caregivers of people living with dementia. Presentation of the final version of the iSupport-BR effects evaluation protocol, which will be used in the Randomized Clinical Trial of the iSupport-BR program. In summary, the study details the development of a methodology for the development of a psychoeducational intervention evaluation protocol and may serve as a future example for other researchers in the development of other empirical intervention evaluation protocols.
Development of an instrument protocol to verify the effectiveness of the iSupport-Brazil program for informal caregivers of people living with dementia
Keywords: Idoso; Cuidadores; Demência; Intervenção baseada em internet; Protocolos clínicos; CIENCIAS DA SAUDE